2023
DOI: 10.4103/lungindia.lungindia_182_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pre-extensively drug-resistant tuberculosis (Pre XDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) among extra pulmonary (EP) multidrug resistant tuberculosis (MDR-TB) at a tertiary care center in Mumbai in pre Bedaquiline (BDQ) era

Abstract: Background: Drug-resistant tuberculosis (DR-TB) is the most exigent and calamitous challenge encountered in treatment of TB. Extra pulmonary (EP) DR-TB poses a complex diagnostic and therapeutic challenge owing to myriad of presentations and paucibacillary nature. Data available on this subset is limited. We studied the prevalence of EPDR-TB cases among the total DR-TB cases visiting our Programmatic management of Drug-Resistant TB (PMDT) site. We also studied the demographic and microbiological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In Ecuador, among 21 isolates investigated in 2023, 15 (71.4%) were MDR, and 2 (9.5%) were XDR, rates that almost match our findings [23]. In a 2023 study in India, of 64 isolates, 43 (67.1%) were identified as MDR and 2 (3.1%) as XDR [24].…”
Section: Discussionsupporting
confidence: 86%
“…In Ecuador, among 21 isolates investigated in 2023, 15 (71.4%) were MDR, and 2 (9.5%) were XDR, rates that almost match our findings [23]. In a 2023 study in India, of 64 isolates, 43 (67.1%) were identified as MDR and 2 (3.1%) as XDR [24].…”
Section: Discussionsupporting
confidence: 86%
“…It Is interesting to note that a higher number of pre-XDR-TB and XDR-TB cases were diagnosed in the adult (16-59 years) age group. Independent studies in Bangladesh and India also reported an increased prevalence of pre-XDR-TB among the 21-30 and 18-25 age groups, respectively [13,18]. Moreover, the prevalence of FLQ and SLID resistance TB was notably higher in individuals aged 16-59, especially among males compared to females.…”
Section: Plos Onementioning
confidence: 95%
“…pre-XDR-TB and 8% for XDR-TB [17]. In contrast, previous studies have shown divergent rates, with India reporting a pre-XDR-TB rate of 56%, China at 34%, and Bangladesh at 16% [13,18,19]. Similarly, multi-center studies of MDR-TB patients across eight nations and Poland found a comparable rate of XDR-TB, with 6.7% and 6.4%, respectively [20,21].…”
Section: Plos Onementioning
confidence: 99%